Mengkaji Tahap Perlaksanaan MS ISO 9002 dan Kesannya Terhadap Produktiviti dan Kualiti Jabatan Pertanian Daerah-Daerah di Negeri Kedah - Abdul Rashid, Hamid (2003)
The survey is conducted to investigate the phase of activity MS ISO 9002 implementation and their effectiveness to the productivity and quality of Jabatan Pertanian in the district of Kedah. The concept of excellent quality management practices is operationalized by the following construct : staff commitment to the department, strategic quality process control and productivity. A research framework was developed and three hyphotheses were posited and tested. Data was collected through secondary data and using structured questionnaires. This study employed disproportionate stratified inclusion in the sample. Thirty five respondents from Pejabat Pertanian Daerah in Kedah participated in this study. Descriptive analyses and statistical analysis used were the Pearson correlation, mean and standard deviation. The results revealed that each of the phase of activity MS ISO 9002 implementation construct has a significant relationship with the productivity and quality of the Jabatan Pertanian in the district of Kedah. Using Pearson correlation analyses, all variable shown positive correlation whereas the highest corellation is focus towards farmer with r = 0.633 and the lowest correlation is quality training with r = 0349. Descriptive analyses through mean and standard deviation also shown focus towards farmer is the highest with mean 4.5486. Amongst the constructs, focus towards farmer, strategic quality planning and focus towards workers have very significant and positive relationship with the productivity. Therefore, these three variables deserve to be monitored and tailored appropriately in order to enhance Jabatan Pertanian productivity and quality. In conclusion, this study provides an insight into further understanding on how to enhance organizational productivity and quality, in order to improve farmers standard of living.